Manifestasi Dakwah Kiai Chaidar Idris dalam Menanamkan Kesadaran Berpolitik Masyarakat Wonosobo - Dewi Fatimah Zahro (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
The role of a Kiai is interesting to review because Kiai has a complex political perspective. It is hoped that the kiai will have a great influence and can increase public participation to participate in choosing leaders who can guide each of their policies. Wonosobo Regency is one of the regencies located in Central Java Province, has a population that is predominantly Muslim. With the majority being Muslim, Islamic culture affects people's lives. With this great influence of Islamic culture, it has affected the obedience and trust of the people to one of the leaders, namely the kiai. Kiai are more trusted and obeyed by the community. In this study, researchers used a qualitative approach. In addition to using data collection techniques in the form of interviews, researchers also used data collection techniques through observation. The results of this study show. The role of Kiai Chaidar Idris is to be able to increase public awareness of politics in order to welcome the elections in 2024 with activities that approach students and the community. The activities carried out by Kiai Chaidar Idris include being a mosque imam, conducting Fajr lecture studies, and carrying out discussion activities. Kiai Chaidar Idris did not forget to include an invitation not to do Golput or the white group in some of his lectures. Which is a form of implementation to make people in Wonosobo Regency aware to participate in politics, especially approaching the 2024 general election.